Endometrial cancer in young woman: Adenokarcinom endometrija pri mladi ženski - Repše Fokter, Alenka (Acta Medico-Biotechnica, 2021)
Purpose: Endometrial cancer is a common malignant disease for which there is no cost-effective early detection screen. Endometrial cancer primarily affects older women and is usuallydiagnosed after symptoms occur. This malignancy is extremely rare in women younger than 40-years-old, so it is rarely considered, especially in asymptomatic cases. Endometrial cells should be evaluated and reported in cervicovaginal smears, but the sensitivity and positive predictive value of Pap tests for the detection of endometrial carcinoma is low.Case report: This is a case report of a 30-year-old asymptomatic woman who was invited for regular cervical cancer screening and had irregular menstrual periods and was overweight. A Pap test revealed atypical endometrial cells, suspicious for carcinoma. Polycystic ovaries and a thickened endometrium were diagnosed following ultrasound investigation. Endometrial biopsy was performed, and endometrioid adeno-carcinoma was diagnosed. The patient underwent total hysterectomy with bilateral salpingo-oophorectomy and pelviclymphadenectomy. Pathological examination showed well differentiated adenocarcinoma of endometrioid type with 2 mm of myometrial invasion.Conclusions: Although rare, endometrial carcinoma can occur in younger women. The presence of atypical endometrial cells can be helpful for detecting such cases, but requiresfurther diagnostic assessments. However, it is important for clinicians to know that normal Pap smear results do not rule out this endometrial cancer.
Keywords: pap smear; atypical endometrial cells; endometrial adenocarcinoma; young patients